2022
DOI: 10.1080/21645515.2022.2048559
|View full text |Cite
|
Sign up to set email alerts
|

The association between adverse reactions and immune response against SARS-CoV-2 spike protein after vaccination with BNT162b2 among healthcare workers in a single healthcare system: a prospective observational cohort study

Abstract: Adverse reactions after vaccination with COVID-19 mRNA vaccines are common; however, the association between adverse reactions and humoral responses is uncertain. To determine whether humoral immune responses after BNT162b2 vaccine administration were associated with local and systemic adverse reactions, we conducted a prospective observational cohort study in a single tertiary referral center. Healthcare workers who received the first dose of BNT162b2 vaccine were recruited. SARS-CoV-2 anti-spike IgG antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Two patients had more than on COVID-19 related uveitis events (Patient #3 after the second dose; and Patient #1 after the third booster dose). The precise mechanisms for higher reactogenicity after the second or subsequent doses of Covid-19 mRNA vaccine are still unclear, but several studies have shown that systemic adverse reactions after the second dose are associated with higher levels of anti-spike IgG protein in the serum post-vaccination (41)(42)(43)(44). This higher levels of anti-spike IgG protein has been reported to correlate with increased naïve and transitional B cells and activated CD8+ T cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Two patients had more than on COVID-19 related uveitis events (Patient #3 after the second dose; and Patient #1 after the third booster dose). The precise mechanisms for higher reactogenicity after the second or subsequent doses of Covid-19 mRNA vaccine are still unclear, but several studies have shown that systemic adverse reactions after the second dose are associated with higher levels of anti-spike IgG protein in the serum post-vaccination (41)(42)(43)(44). This higher levels of anti-spike IgG protein has been reported to correlate with increased naïve and transitional B cells and activated CD8+ T cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…The antibody titers of ICSs can be affected by age, sex, and smoking. Jubishi et al reported that self-reported asthma was correlated with elevated anti-Spike IgG levels [ 11 ]. In our study, we did not show the increase of antibody titer in asthma patients.…”
Section: Discussionmentioning
confidence: 99%
“…First among them is the strong immunogenic nature of ionizable cationic phospholipids 94,137 . For example, after injection of the Pfizer‐BioNTech or Moderna COVID‐19 mRNA vaccines, various symptoms including swelling, pain, chills, and fever have been reported 138–140 . These are suspected to be the consequence of the production of pro‐inflammatory cytokines such as IL‐1β and IL‐6 141–143 .…”
Section: In Vivo Delivery Systems For Mrna Vaccinesmentioning
confidence: 99%
“…94,137 For example, after injection of the Pfizer-BioNTech or Moderna COVID-19 mRNA vaccines, various symptoms including swelling, pain, chills, and fever have been reported. [138][139][140] These are suspected to be the consequence of the production of pro-inflammatory cytokines such as IL-1β and IL-6. [141][142][143] Second, an increasing number of studies has verified the immunogenicity of PEG; therefore, repeated administration of PEG can induce allergic reactions.…”
Section: Lnpmentioning
confidence: 99%